Evaluation Of Coffee Supply Chain Performance Using Value Chain Analysis And Fishbone Diagram (Case Study On Coffee Farmers In East Java) - Amilia Azzahro; Syarifa Hanoum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Coffee has grown into a high-value commodity in international trade, contributing significantly to global GDP and creating millions of jobs worldwide. This study aims to analyze the value chain of the coffee industry in East Java, identify the root cause of the low margins obtained by coffee farmers, and provide recommendations to increase their income and efficiency in the supply chain. The methodology used included primary data collection through in-depth interviews with coffee supply chain actors in East Java and analysis using fishbone diagrams to identify factors causing low margins of coffee farmers, such as limited market access, inadequate processing equipment, and conventional drying methods. The results of the study show that coffee farmers get the lowest profit margin, less than 10%, due to low efficiency and productivity. The recommendations included digital technology training, financial assistance for equipment, and low-interest credit programs for coffee farmers. The implementation of this recommendation is expected to increase the efficiency, productivity, and profit margins of coffee farmers in East Java, increasing their competitiveness in the global market. The study also highlights the need for multi-stakeholder support and long-term evaluation to measure the effectiveness of proposed interventions.